Application of cryopreservation for the conservation of plant genetic resources and stock cultures, virus eradication and tool for breeding - Panis, Bart (2023)
COPYTREE: INNOVATIVE WOODY PLANT CLONING FIRST CONFERENCE OF COST ACTION CA21157 17 & 18 April 2023 Faculty of Chemistry (USC) Santiago de Compostela, SPAIN